Upaya Meningkatkan Hasil Belajar Murid Kelas V Tema 5 Sub Tema Komponen Ekosistem Melalui Model Talking Stik Pada SD Negeri Jaman Kecamatan Mutiara Kabupaten Pidie - Fitria (Journal of Technology and Literacy in Education, 2022)
Teaching and learning activities do not always go as desired, because the success of teaching and learning is influenced by many factors, one of which is the learning approach used by the teacher in teaching. This also happened at SD Negeri Jaman, where most of the teachers still carried out teaching and learning activities using the lecture method so that students felt bored and bored. This could affect student learning outcomes, so that many students did not finish. Based on the problems mentioned above, the researcher will conduct a classroom action research that refers to the model developed by Kemmis and Mc Taggart which consists of planning, action, observation, and reflection stages. This study aims to increase the activity and learning outcomes of Equilibrium Material in fifth grade students at SD Negeri Jaman Kec.Mutiara through the Talking Stick Learning Model. This research was conducted for three months in semester I of the 2022/2023 school year where the research subjects were Class V students of SD Negeri Jaman Kec.Mutiara, a total of 18 students. The data obtained for research were in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis it was found that by using the talking stick learning model there was an increase in student learning outcomes in each cycle where in the pre-cycle the average class value was 40.83 with 38.89% mastery learning, and in cycle I the average value increased to 60,67 with a completeness level of 38,89% and continued to increase in cycle II to 70,66 with learning mastery reaching 94,4%. Likewise, teacher and student activities continue to increase in each cycle. The conclusion from the study is that the learning process using the Talking stick learning model is proven to be able to improve learning outcomes